Nutrition in Lao PDR : Causes, Determinants, and Bottlenecks - World Bank Group (World Bank, Vientiane, 2016)
Under nutrition levels in Lao PDR remain among the highest in the world, despite both rapid economic growth and a significant decline in poverty over the past years. Concerns about the slow progress in reducing under nutrition have triggered intense policy discussion and several analytical reports have been produced over the last few years on the Lao PDR nutrition crisis and its drivers. This policy note provides an overview of the size, severity, and key determinants of child under nutrition in Lao PDR and proposes recommendations for the scale-up of programs and interventions to strengthen the overall response to under nutrition in the country. The note draws from a multivariate analysis of determinants of stunting in addition to descriptive statistics of nutrition-related behaviors and outcomes in the country, using recent surveys. These analyses are complemented with findings from the recent qualitative-based rapid assessment of nutrition counseling and growth monitoring conducted during the early months of 2016 in selected provinces, to contextualize findings within the health sector’s capacity to deliver preventive and curative nutrition services.